2003
DOI: 10.1051/vetres:2003024
|View full text |Cite
|
Sign up to set email alerts
|

The bovine neutrophil: Structure and function in blood and milk

Abstract: -Migration of polymorphonuclear neutrophil leukocytes (PMN) into the mammary gland provide the first line of defense against invading mastitis pathogens. Bacteria release potent toxins that activate white blood cells and epithelial cells in the mammary gland to secrete cytokines that recruit PMN that function as phagocytes at the site of infection. While freshly migrated PMN are active phagocytes, continued exposure of PMN to inhibitory factors in milk such as fat globules and casein, leads to altered PMN morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(134 citation statements)
references
References 149 publications
(171 reference statements)
4
128
0
2
Order By: Relevance
“…PMNs are the most important immune cells as the first line of cellular defence against acute inflammatory reaction (Paape et al 2003). PMNs have been detected in the CL in cows, humans and rats during the oestrous (menstrual in humans) cycle and early pregnancy (Brannstrom et al 1994, Best et al 1996, Brannstrom & Friden 1997, Jiemtaweeboon et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…PMNs are the most important immune cells as the first line of cellular defence against acute inflammatory reaction (Paape et al 2003). PMNs have been detected in the CL in cows, humans and rats during the oestrous (menstrual in humans) cycle and early pregnancy (Brannstrom et al 1994, Best et al 1996, Brannstrom & Friden 1997, Jiemtaweeboon et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…neutrophils) is originated from the blood through the chemotaxis and diapedesis in response to a local aggression (Paape et al 2003). With this in mind, it is well known that the percentage of neutrophils markedly increased during IMIs (Pyörälä 2003, Mira et al 2013, as demonstrated here by the positive correlation between the milk SCC and the percentage of milk PMNs.…”
Section: Discussionmentioning
confidence: 61%
“…With this in mind, variations among cows in neutrophil activity might explain differences in susceptibility of the mammary gland to infection (Paape et al 2003). Regarding our results, it is possible to measure the presence of the PMNs targeting the immune function, which could help in the development of a new method to select cow with a better immune response, although more studies are necessary.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Inflammatory response during mastitis is marked by the increased blood flow in infected tissue, increased vascular permeability, leukocyte migration from blood vessels into interstitial space and accumulation of leukocytes at the site of trauma (Tkalčević and Hrvačić, 2011). Bacteria release toxins which activate leukocytes and epithelial cells in the mammary gland to release cytokines which attract numerous polymorphonuclear leukocytes (PMN) functioning as phagocytic cells at the site of infection (Paape et al, 2003). PMN such as neutrophils and macrophages are the first cells infiltrating the site of trauma (Wellnitz et al, 2012).…”
Section: Pathogenesis Of Mastitismentioning
confidence: 99%